Gas chromatography-mass spectral structural analysis, phytochemical screening and antimicrobial activity of n-hexane leaf extract of Corymbia torelliana - Moses Daben, Janet; Albert Dashak, Dayil; Uwhomagbejo Isaac, Rahab (International Journal of Advanced Chemistry, 2017)
The chemical studies and antimicrobial activity of n-hexane leaf extract of Corymbiatorelliana was evaluated for medicinal importance. The phytochemical constituents present were steroids, tannins, cardiac glycosides alkaloids and terpenes. The result of sodium fussion test revealed the presence of Phosphorus Nitrogen and Chlorine. The Column Chromatography gave several fractions that were pulled together by Thin Layer Chromatography based on their Rf values, colours and resolutions on different solvent systems. GC-MS was used to identify compounds like: Hexadecanoic acid methyl ester, 9,12-Octadecadienoic acid methyl ester, 2,2,4,4-tetramethyl-1,3-cyclobutanediene, Pentadecanoic acid-14-methyl methyl ester, Hexadecanoic acid-2-hydroxyl propyl ester, 2(4H)-Benzofuranone-5,6,7,7a-tetrahydro-4,4,7a-trimethyl and many others. Antimicrobial screening was carried out on Escherichia coli, Staphylococcus aureus and Aspergillus niger using the agar well diffusion technique. The result shows that the extract exhibit antimicrobial activity with zones of inhibition in diameter. These results show that the plant exhibit antimicrobial activity and possess pharmacological characteristics, which could be applied in the production of potent drugs.